2013
DOI: 10.1021/es4040864
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Materials Genome Into Safer Consumer Products

Abstract: F ive years after legislation to establish the Green Chemistry Initiative (GCI), the landmark California Safer Consumer Products Law became effective on October 1st, 2013. 1 We argue here that the development of new regulatory policies to stimulate the convergence of materials development research and public health and environmental impact assessments provides evidence that these topics have traditionally addressed separate audiences, developed different values and measurement systems, and focused on incompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(2 reference statements)
0
5
0
Order By: Relevance
“…The results of the chemical life cycle impact assessment of e-waste ash presented here provides new information that may be used to support confirmatory assessments linking specific exposures to disease outcomes, and to support design-for-the-environment strategies [44].…”
Section: Assessment Of Environmental and Human Health Impacts Of E-wamentioning
confidence: 89%
“…The results of the chemical life cycle impact assessment of e-waste ash presented here provides new information that may be used to support confirmatory assessments linking specific exposures to disease outcomes, and to support design-for-the-environment strategies [44].…”
Section: Assessment Of Environmental and Human Health Impacts Of E-wamentioning
confidence: 89%
“…Given the popular demands for innovation in the mobile phone industry, it is likely that the use of "high tech" materials in manufacturing will continue to increase. Many of these materials will be untested in terms of resource depletion, and potential impacts on environmental quality and human health (Ogunseitan et al, 2013;Ogunseitan and Schoenung, 2012). The United Nations reported that approximately 45 million metric tons (Mt) of e-waste was generated globally in 2016, an 8% increase from 2014 level, and predicted further increase to 21% by 2021 (Baldé et al, 2017;Singh et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…47,48 The California Safer Consumer Products (SCP) program, enacted in 2008 as the Green Chemistry Law aimed to reduce the use of hazardous chemicals and to accelerate the quest for safer alternative chemicals used in consumer products. 49 The law authorized the California EPA's Department of Toxic Substances Control (DTSC) to develop and implement proactive regulations designed to restrict the use of hazardous chemicals in products meant for the California marketplace. As of December 2022, there are 3315 candidate chemicals defined as ones that exhibit a hazard trait and/or an environmental or toxicological endpoint and are identified in one or more authoritative lists generated by other reputable agencies, including, for example, the list of chemicals known to cause cancer and/or reproductive toxicity and listed under California's Health and Safety Code section 25249.8 of the California Safe Drinking Water and the 1986 Toxic Enforcement Act.…”
Section: Proactive Regulatory Policies As Tools For Managing Chemicalsmentioning
confidence: 99%